The multi-spacecraft high-energy solar particle event of 28 October 2021 - Kouloumvakos, A. (EDP Sciences, 2025)
Aims. We studied the first multi-spacecraft high-energy solar energetic particle (SEP) event of solar cycle 25, which triggered a ground level enhancement on 28 October 2021, using data from multiple observers (Parker Solar Probe, STEREO-A, Solar Orbiter, GOES, SOHO, BepiColombo, and the Mars Science Laboratory) that were widely distributed throughout the heliosphere and located at heliocentric distances ranging from 0.60 to 1.60 AU.
Methods. We present SEP observations at a broad energy range spanning from ∼10 to 600 MeV obtained from the different instruments. We performed detail modelling of the shock wave and we derived the 3D distribution and temporal evolution of the shock parameters. We further investigated the magnetic connectivity of each observer to the solar surface and examined the shock’s magnetic connection. We performed velocity dispersion analysis and time-shifting analysis to infer the SEP release time. We derived and present the peak proton flux spectra for all the above spacecraft and fluence spectra for major species recorded on board Solar Orbiter from the Suprathermal Ion Spectrograph (SIS). We performed 3D SEP propagation simulations to investigate the role of particle transport in the distribution of SEPs to distant magnetically connected observers.
Results. Observations and modelling show that a strong shock wave formed promptly in the low corona. At the SEP release time windows, we find a connection with the shock for all the observers. PSP, STEREO-A, and Solar Orbiter were connected to strong shock regions with high Mach numbers (>4), whereas the Earth and other observers were connected to lower Mach numbers. The SEP spectral properties near Earth demonstrate two power laws, with a harder (softer) spectrum in the low-energy (high-energy) range. Composition observations from SIS (and near-Earth instruments) show no serious enhancement of flare-accelerated material.
Conclusions. A possible scenario consistent with the observations and our analysis indicates that high-energy SEPs at PSP, STEREO-A, and Solar Orbiter were dominated by particle acceleration and injection by the shock, whereas high-energy SEPs that reached near-Earth space were associated with a weaker shock; it is likely that efficient transport of particles from a wide injection source contributed to the observed high-energy SEPs. Our study cannot exclude a contribution from a flare-related process; however, composition observations show no evidence of an impulsive composition of suprathermals during the event, suggestive of a non-dominant flare-related process. © The Authors 2024.